1997
DOI: 10.1088/0029-5515/37/3/i04
|View full text |Cite
|
Sign up to set email alerts
|

The m=2, n=1 mode suppression by ECRH on the T-10 tokamak

Abstract: Experiments on m=2, n=1 tearing mode suppression and on avoidance of density limit disruptions by electron cyclotron resonance heating (ECRH) were performed on the T-10 tokamak. Partial suppression of the m=2, n=1 mode by the high frequency (HF) power deposition in the vicinity of the q=2 surface was observed. Development of external kink modes with HF power injection can result in m=2, n=1 mode destabilization under specific operating conditions. ECRH suppresses m=2, n=1 mode activity at extremely high values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…The experimental results suggest that the fast electron transport coefficient is much larger than the neoclassical one. 35,37,38 Assuming for a reactor plasma with plasma density nϭ5 ϫ10 19 m Ϫ3 , the fast electron temperature 50 keV, a ϭ2.0 m, and Ќf ϭ1.0 m 2 /s, it is found that f ϭ0.30 ϫ10 3 s and w pt /aϭ2.9ϫ10 Ϫ2 . Such a w pt value is comparable with the rf wave deposition width, and therefore f is an important parameter in determining the stabilizing effect.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results suggest that the fast electron transport coefficient is much larger than the neoclassical one. 35,37,38 Assuming for a reactor plasma with plasma density nϭ5 ϫ10 19 m Ϫ3 , the fast electron temperature 50 keV, a ϭ2.0 m, and Ќf ϭ1.0 m 2 /s, it is found that f ϭ0.30 ϫ10 3 s and w pt /aϭ2.9ϫ10 Ϫ2 . Such a w pt value is comparable with the rf wave deposition width, and therefore f is an important parameter in determining the stabilizing effect.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The perpendicular transport of the fast electrons broadens the driven current profile and leads to a smaller local current density. 37,38 This effect is measured by the parameter w pt ϭ( Ќf / f ) 1/2 . 39 The total width of j d is approximately given by w d Ϸw ds ϩw pt .…”
Section: B Effect Of the Fast Electron Slowing Down Time For MCDmentioning
confidence: 99%
“…3 NTM suppression experiments have been performed successfully using both ECRH and ECCD. [4][5][6][7][8][9][10][11][12][13][14] The generalized Rutherford equation (GRE) 15,16 provides a theoretical model for the growth and stabilization of tearing modes. It describes the nonlinear temporal evolution of the full width w of the associated magnetic island as a function of different stabilizing and destabilizing mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the T-10 tokamak, the microwave radiation at the first and second ECR harmonics was used for this purpose [8,9]. changes in the character of the sawtooth oscillations related to the development of the internal disruptive instability during variation in the location of the ECR region with respect to the resonance surface q = 1, where q is the stability margin, due to the plasma-column displacement along the large radius.…”
Section: Influence On the Large-scale Magnetohydrodynamic Instabilitiesmentioning
confidence: 99%